Discussion on the Etiology and Pathogenesis of Eczema from the Perspective of Zangxiang Theory - Li, Xi; Chen, Zhenlin (Journal of Contemporary Medical Practice, 2025)
Wet eczema corresponds to eczema in Western medicine and represents one of the most common and challenging conditions in dermatology. It is characterized by recurrence, pruritus, exudation, symmetry, polymorphic lesions, and a tendency toward chronicity. Western medical treatment primarily relies on corticosteroids and antihistamines, but therapeutic effects are inconsistent, and significant adverse reactions often occur after discontinuation of corticosteroids. Therefore, compared with Western medical treatment, TCM syndrome differentiation treatment offers distinct characteristics and advantages. Taking the theory of Zangxiang as the main entry point, this paper explores the etiology and pathogenesis of wet eczema from the perspective of Zangxiang, aiming to better understand and treat eczema from the aspects of etiology and pathogenesis.